Exact Evaluation of Infinite Series Using Double Laplace Transform Technique - Hassan Eltayeb; Adem Kılıçman; Said Mesloub (Abstract and Applied Analysis)
Double Laplace transform method was applied to evaluate the exact value of double infinite series. Further we generalize the current existing methods and provide some examples to illustrate and verify that the present method is a more general technique.